Comparative Analysis of the Role of Gender Equality in Environmental, Social, and Governance Performance Across Belgium, Denmark, Luxembourg, and Hungary - Gergely, Beatrix Katalin; Sipos, Dóra; Zseni, Anikó (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
This paper examines the impact of gender equality on the Environmental, Social, and Governance (ESG) performance of Belgium, Denmark, Luxembourg, and Hungary, focusing on the proportion of women in leadership positions. Utilizing a comparative, index-based approach, the research evaluates data from 2011 to 2021 using indicators such as the Sustainable Development Goals (SDG5), Human Development Index (HDI), and Social Progress Index (SPI). Findings reveal that Belgium and Denmark exhibit the highest gender equality progress in leadership, while Hungary lags despite minor improvements. Contradictions between national and European statistical data highlight discrepancies in reporting methodologies, particularly regarding the public and private sectors. The paper examines the correlation between higher female representation in leadership and improved ESG performance, suggesting that increased gender diversity contributes to corporate sustainability. Research limitations include data inconsistencies across statistical sources and the exclusion of sector-specific analyses. The findings provide valuable insights for policymakers and corporate governance stakeholders, reinforcing the necessity of achieving the EU-mandated 40% female leadership quota by 2026. The paper’s originality lies in its comprehensive, multi-index evaluation, offering a nuanced perspective on gender equality’s role in ESG performance within the examined European countries.